If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 = -25x Solving 100 = -25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25x' to each side of the equation. 100 + 25x = -25x + 25x Combine like terms: -25x + 25x = 0 100 + 25x = 0 Add '-100' to each side of the equation. 100 + -100 + 25x = 0 + -100 Combine like terms: 100 + -100 = 0 0 + 25x = 0 + -100 25x = 0 + -100 Combine like terms: 0 + -100 = -100 25x = -100 Divide each side by '25'. x = -4 Simplifying x = -4
| x(x)-6x=-9 | | (2x-1)(x-2)= | | -8.5+7n=4.1 | | y-24=3y-20 | | (2x+1)(x-2)= | | (2x+1)(x+2)= | | x(x)+3x+2=0 | | 3g-11=10 | | 2h+20=52 | | 7g-8=-29 | | -15-7x=6 | | 5y-3x=0 | | 7p+8=-29 | | 7x+8=-29 | | (8x+2)(x-14)= | | 12+6b=-18 | | (x+9)(x-36)= | | -3+4x=29 | | 2.5x^2=25x | | 3(x-5)+5=5x-2(3+x) | | 6m+5-7m=10-5m+3 | | (4x-16)(2x+3)= | | 9(3n-2)=(7n+7)+7 | | y(y)+8y+7=0 | | 8y+3(y-7)=3(y+2)-2 | | 2(3x-6)+9=6x-3 | | 6/-3= | | 6x-4=6(x+5) | | -12/14= | | 8b-5b-b= | | 47=2x+4x-1 | | 6x+5=-5+4x+20 |